Tephra influence on glacier ablation in Iceland - Möller, Rebecca (2019)
Among the active volcanoes around the world, approximately one third is covered by perennial snow or ice or is at least located close to glacierized terrain. Explosive eruptions from such volcanoes have the capability to affect extensive glacier areas with fallout of volcanic materials. The resulting supraglacial particle depositions are known to effectively alter the energy balance at the glacier surface. The decreased albedo leads to increased amounts of absorbed energy from the atmosphere, but thermal resistance of the supraglacial deposits hampers the conduction of this energy down to the glacier ice. The counteracting nature of these two effects leads to a high level of complexity and spatial variability in the influences on ablation which are exerted by volcanic fallout. A region of the world where this issue is of particular importance even beyond purely environmental concerns is Iceland. The proximity of major infrastructure installations to active volcanism and wide-spread glaciation and the fact that more than two thirds of all electricity generation on the island comes from predominantly meltwater-fed hydropower plants induces a globally unparalleled socio-economic relevance. This thesis follows an interdisciplinary approach combining methods from geology and physical geography to answer specific research questions that are related to recent eruptions of the Icelandic volcanoes Eyjafjallajökull and Grímsvötn. The influence of volcanic fallout and resulting tephra deposition from these volcanoes on neighboring ice caps is studied with respect to changes in glacier albedo pattern and glacier ablation. Individual links of a modeling chain are presented that reproduce related aspects and processes. Glaciological fieldwork was carried out on Iceland in the period 2013-2016. The data obtained serve as a basis for the development of models of ablation variability under the influence of covers of volcanic materials. New remote sensing-based approaches are developed that quantify changes of glacier albedo ...